PEMANFAATAN LIMBAH KAIN KHAS SUMATERA SELATAN SEBAGAI MEDIA PEMBELAJARAN KEWIRAUSAHAAN - Masnunah; Dian Neta Lestari; Riswan Aradea (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
The problem of this research is how to use songket cloth waste and typical South Sumatra jumputan as a media for entrepreneurship learning. The purpose of this research is to find out motivation and to foster an entrepreneurial spirit in students, in the use of Songket and Jumputan cloth waste typical of South Sumatra as Entrepreneurship Learning Media for Semeter IV students at PGRI Palembang University for the 2019/2020 Academic Year. Descriptive research method, this method is carried out in various steps, namely from planning, processing, marketing, evaluation to plow up. The results of the research on the use of songket and jumputan fabric waste as a medium for learning entrepreneurship, showed that there was motivation and the growth of an entrepreneurial spirit in students, it was seen from the average response of students to the questionnaire that was given was classified as very high, which was 79.44%. Based on the student question indicator which consists of 5 indicators; designing products for 79.36% in the very high category. The indicator for processing products is 77.49%, the indicator for marketing the product is 78.67%, the indicator for developing a product is 79.87% and the indicator for preserving, maintaining the product or enthusiasm is 81.82% in the very high category.